The Effect of Circuit Training on Improvement in Futsal Athletes: Literature Review - Jatra, Rices; Wati, Sandra Zahara; Kumara, Alif Rengga; Rinaldi, Muhammad Wahyu; Fernado, Ricky (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Futsal is a high-intensity, intermittent sport from the beginning to the end of the match. Futsal players must have anthropometric and somatotype characteristics that match the needs of high-intensity intermittent training, as well as good physical condition on the dominant physical aspect, so that players' performance during competition and physiological losses after competition can be minimised to the greatest extent possible. aspects of physical condition as an opportunity for coaches to control player performance through training models. This research is a literature review study that aims to reveal the presence or absence of the influence of circuit training on the improvement of futsal athletes. Using the Google Scholar database, enter the keyword "The Effect of Circuit Training Exercise on the Improvement of Futsal Athletes" to collect various references and references that are relevant to the topic of the problem being studied. From the results of the search for sources in the database, 15 articles were found published in 2014–2021. The conclusion of this study shows that "There is an effect of circuit training on the improvement of futsal athletes," so that it can be used as a study and input. Coaches and athletes can use circuit training exercises as one of them.